Terminuotų darbo sutarčių teisinio reguliavimo ypatumai pagal Lietuvos teisę - Bubilaitytė, Beata (Teisė, 2008)
The purpose of this paper is to explore and to analyse peculiarities of Lithuanian legal regulation of fixed-term employment agreement. Peculiarities are divided into four groups: peculiarities of concept of fixed-term employment agreement, peculiarities of conclusion, performance and expiry of fixed-term employment agreement. Specific essential conditions for conclusion of a fixed-term employment contract are: the term of an employment contract (if the parties to the contract have used both methods to define the term, one of them must be chosen as a prevailing one) and the circumstance that legal acts must allow to conclude it at all. The performance of a fixed-term employment contract according to Lithuanian labour law is not that specific compared to the performance of other employment contracts. Peculiarities of the expiry of fixed-term employment contract are: firstly, only the will to terminate fixed-term employment contract does end the employment contract at all. Otherwise, the expiry of the term of an employment contract will end only the fixed-term employment contract but not the employment contract itself. Secondly, the law does not make it clear, whether restrictions on the termination of an employment contract must be applicable to fixed-term employment agreements. Lithuanian legal doctrine does believe that they should, but Lithuanian Supreme Court says that they should not.